2018
DOI: 10.1002/1878-0261.12394
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of nano‐particulated, water‐soluble erlotinib against intracranial metastases of EGFR‐mutant lung cancer

Abstract: Central nervous system (CNS) metastasis is one of the serious complications of epidermal growth factor receptor (EGFR)‐mutant lung cancer, which arises due to poor penetration of the brain–blood barrier by EGFR‐tyrosine kinase inhibitors (EGFR‐TKIs). Although osimertinib, a third‐generation EGFR‐TKI, has efficacy against CNS metastases, further treatment modalities are still needed as some of these lesions do not respond to osimertinib, or undergo progression after an initial response to this drug if radiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Moreover, nowadays, there are advanced novel immunotherapies and targeted therapies that was reported to show increased blood–brain barrier penetration and realize high response rates and more durable control of BM, and advances in radiotherapies and minimally invasive surgical techniques, which are thought to improve the survival outcome of patients with BM 7,17 . For example, EGFR/ALK TKIs had significant intracranial activity and could achieve longer intracranial progression free survival, higher overall response rate than chemotherapy or radiotherapy, which have been proved in many retrospective and prospective studies 18–22 . And some studies have confirmed that stereotactic radiotherapy (SRS) was a well‐tolerated safe option for patients with four or more BM 23–25 .…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, nowadays, there are advanced novel immunotherapies and targeted therapies that was reported to show increased blood–brain barrier penetration and realize high response rates and more durable control of BM, and advances in radiotherapies and minimally invasive surgical techniques, which are thought to improve the survival outcome of patients with BM 7,17 . For example, EGFR/ALK TKIs had significant intracranial activity and could achieve longer intracranial progression free survival, higher overall response rate than chemotherapy or radiotherapy, which have been proved in many retrospective and prospective studies 18–22 . And some studies have confirmed that stereotactic radiotherapy (SRS) was a well‐tolerated safe option for patients with four or more BM 23–25 .…”
Section: Discussionmentioning
confidence: 94%
“…synthesized water-soluble erlotinib (NUFS-sErt) by using a nano-particulation platform technology utilizing fat and supercritical fluid (NUFS™) to resolve the low solubility problem that typically prevents the creation of injectable forms of EGFR-TKIs. The effects of NUFS-sErt were similar to those of conventional erlotinib in terms of inhibiting the proliferation of EGFR-mutant lung cancer cells and suppressing EGFR signaling ( 90 ). By prolonging circulation time, improving drug solubility, and overcoming drug resistance, Nanotechnology-based targeted therapy has shown great promise for the treatment of advanced lung cancer.…”
Section: Nanotechnology-based Therapeutics For Lung Cancermentioning
confidence: 88%
“…Based on these findings, a phase II/III clinical trial to evaluate this strategy in patients with recurrent GBM (NCT03025893) is ongoing with sunitinib dosing of 700 mg once every 2 weeks. Alternative approaches such as intrathecal TKI injection may also be considered to optimize local exposure, but this has been studied only in a preclinical model with nano-particulated, water-soluble erlotinib (39). Besides achieved drug concentrations at the target site, the signaling context or network in tumors is essential for TKI efficacy as well (40,41).…”
Section: Discussionmentioning
confidence: 99%